New descriptions, synonymies and records in South American Lamiinae(Coleoptera, Cerambycidae) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2023)
Two new species are described from Ecuador: Colobothea androwi sp. nov. and Tybalmia diffusa sp. nov. A provisional key to species of Tybalmia Thomson, 1868 is provided. Tybalmia tetrops Bates, 1872 is synonymized with T. mydas (Lucas, 1859), and a new state record in Brazil is provided. Tybalmia orbis Dillon & Dillon, 1945 is synonymized with T. pupillata (Pascoe, 1859), and a new country record is provided.